Dietary antioxidative supplements and diabetic retinopathy; a systematic review - Tabatabaei-Malazy, Ozra (J Diabetes Metab Disord, 2019)
PURPOSE: There is controversial data regarding the effects of dietary antioxidative supplements on diabetic retinopathy (DR). We conducted a systematic review of both observational and randomized controlled clinical trials (RCTs) to clarify whether they are effective or not. METHODS: All observational and RCTs conducted by antioxidative supplements on DR published up to 1 January 2018 in PubMed, Web of Sciences, Scopus and Cochrane Library databases were included. Exclusion criteria were animal studies, and studies conducted in Type 1 diabetes mellitus (T1DM), children or pregnant women. Main outcome measures were reporting the incidence or progression of DR in T2DM by assessment of visual fields, and measurements of oxidative and antioxidative biomarkers. The quality of reporting of included articles and risk of bias were assessed. RESULTS: Finally, we reached 14 observational studies and 7 RCTs that conducted on 256,259 subjects. Due to severe methodological heterogeneity, only qualitative synthesis was carried. All studies were reported a significantly lower level of antioxidants and higher level of oxidative stress biomarkers in DR compared with others. There was an inverse significant correlation between vitamin C and malondialdehyde (MDA) (r = −0.81) or DNA damage (r = −0.41). These figures were statistically significant between vitamin E and MDA (r = 0.77) or superoxide dismutase (r = 0.44). Coefficient of correlation between MDA and zinc (−0.82), coenzyme Q10 (0.56), and magnesium (−0.73) was significant. Multi-oxidants trials were shown non-significant beneficial effects on DR. CONCLUSIONS: Although our study supports the positive effects of antioxidative supplements on DR, more high quality studies are needed to confirm. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40200-019-00434-x) contains supplementary material, which is available to authorized users.